THE RELATIONSHIP OF PLASMA SOMATOMEDIN (IGF-1) WITH PERFORMANCE AND CARCASS CHARACTERISTICS OF AWASSI AND KARADI LAMBS - Khalil A. D. Oray, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Lambs’ performance and some carcass traits in relation to insulin-like growth factor-1 (IGF-1) were studied in twelve lambs from each of Awassi and Karadi slaughtered at three different weights raised at the animal farm, Department of Animal Production, College of Agricultural Engineering Science, University of Duhok.  Each group of lambs slaughtered at 30 kg, 40 kg, and 50kg was kept in an individual separate pen and fed concentrate ration at libitum. Weight gain and feed intake were recorded till the slaughter and blood samples were taken at the beginning of the experiment and one day before slaughter from the vena jugular for the IGF-1 analysis by using the enzyme immunoassay (EIA) method. Statistical analysis showed that the concentrations of insulin-like growth factor (IGF-1) were not affected significantly by breed.  Furthermore, lambs slaughtered at 50 kg, showed numerically the highest IGF-1 concentration, compared to lambs slaughtered at 30 kg and 40kg. There was a significant positive correlation between IGF-1 concentrations and each of the average daily gain and daily feed intake of Awassi lambs slaughtered at 30. Additionally, no consistent results were found between the IGF-1 concentration and carcass composition in studied breeds.